Combined antegrade femur lengthening and distal deformity correction: a case series - Achraf Jardaly; Shawn R. Gilbert (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Leg length discrepancy is often associated with distal femur angular deformities such as valgus or flexion. This study aims to report a new technique for simultaneous limb lengthening and acute distal femoral angular correction. Methods A retrospective chart review of patients undergoing a single procedure was conducted. Patients included had a single operation where they underwent distal femur osteotomy stabilized with a plate followed by antegrade nailing with a magnetically controlled intramedullary lengthening nail (PRECICE, Ellipse Technologies, Inc., Irvine, CA, USA) using a trochanteric entry. Results Seven femurs from 7 patients were included. The average age at operation was 13.6 years, and the leg length difference was 51 mm (range 30–105 mm). Associated deformities were valgus (4), knee flexion contracture (2), and both valgus and flexion contracture (1). Lengthening achieved was 43 mm (P = 0.0036), with a consolidation index of 27 days/cm and reliability of 0.87 (6/7). The 5 patients with angulation had an improvement of valgus from 12 to 4° (P = 0.006) and of the mechanical axis deviation from 34 to 3 mm (P = 0.0001). The range of motion also improved in the 3 patients with contractures. Preoperative gait disturbance, hip and knee pain, and functional scoliosis resolved after the limb deformities were corrected. Conclusion Combining a magnetic internal lengthening nail with a second distal osteotomy stabilized with a plate can successfully correct limb length and distal femur deformity acutely without altering the expected result of each procedure.